(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to contribute to the consolidation of scientific knowledge of compliance control and its role in verifying the proper disposal of funds to manage the wheel of the economy towards achieving targeted development and preserving public money, as well as clarifying the role of tax revenues in strengthening the public treasury and achieving social justice. The analytical descriptive approach was adopted in the process of analyzing The quantitative data collected through personal interviews, and the research reached a set of conclusions, the most important of which is the contribution of compliance control according to its three principles. (Transparency, accountability, and inclusiveness) on the availability of appropriate reports on the proper disposal of tax revenues and accountability for them from misuse, fraud and manipulation, and to take the necessary corrective measures to address breaches in laws, regulations, and instructions, and to hold accountable those who fail to waste it as public money that contributes to replenishing the treasury. The researcher recommended that it should Identifying the parties responsible for non-compliance with laws, regulations, and instructions related to tax revenues in a transparent and clear manner within the oversight report for accountability purposes.